2014
DOI: 10.1089/nat.2013.0479
|View full text |Cite
|
Sign up to set email alerts
|

Non-Clinical Safety Studies of IMT504, a Unique Non-CpG Oligonucleotide

Abstract: IMT504 is a non-CpG 24-mer oligodeoxynucleotide (ODN) with immunomodulatory as well as tissue repair activity. IMT504 has been previously proven to be effective in animal models of vaccine potency, chronic lymphocytic leukemia, tissue regeneration, and sepsis. Here, we assessed the safety, including pharmacokinetics and toxicity studies in rats and monkeys, of IMT504 in a single-or repeated-dose administration by the subcutaneous (SC) or intravenous (IV) routes. In rats, the maximum tolerated dose was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Furthermore, in preclinical toxicity studies, we demonstrated that IMT504 is a very safe drug (17,23). We are presently validating the effects of IMT504 in NOD mice, a spontaneous model of T1D.…”
Section: (46) Demonstrated Increasedmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, in preclinical toxicity studies, we demonstrated that IMT504 is a very safe drug (17,23). We are presently validating the effects of IMT504 in NOD mice, a spontaneous model of T1D.…”
Section: (46) Demonstrated Increasedmentioning
confidence: 74%
“…of doses : 20). Glycemia was measured in tail blood samples in nonfasted conditions on days 1,6,11,17,21,26,29,32,36,41,46,53, and 66 at 11-12 AM (last IMT504 injection on day 40). Intraperitoneal glucose tolerance tests (IPGTT) were performed on day 60.…”
Section: First Experimental Design: Long-term Effects Of Imt504 In DImentioning
confidence: 99%
“…IL-6 has long been known to serve as a predictor of outcome in experimental and human sepsis (26). The capacity to promote granulocyte-macrophage colony-stimulating factor (GM-CSF) expression by IMT504 in the presence of IL-2 might also be involved in the protection of animals from neutropenic sepsis (17). Expression of GM-CSF likely leads to increased production of granulocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IMT504 activates CD4 and CD8 T cells and natural killer cells (NK cells and NKT cells) to promote cellular immune functions with activities against specific forms of cancer and virusinfected cells (15). In addition, preclinical studies indicate an excellent safety profile (16)(17)(18).…”
mentioning
confidence: 99%
“…In addition, formulations of IMT504 are not problematic because IMT504 is highly soluble. Additionally, once injected using different routes, IMT504 has a rapid and broad distribution[364]. Moreover, because IMT504 has good thermal stability, extreme conditions of transport and storage are not necessary.…”
Section: Practical Considerations Regarding the Prospective Clinical mentioning
confidence: 99%